Tindak Tutur Direktif dalam Dialog Film Sweet 20 Sutradara Ody C. Harahap dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Fachrunnisa, Dine Ayu; Juansah, Dase Erwin; Solihat, Ilmi (Peneliti.net, 2024)
This study aims to describe the form and function of directive speech acts in the dialogue of the film Sweet 20 directed by Ody C. Harahap which is then implicated in learning in senior high school. The method used in this research is descriptive method with a qualitative approach. The data were analyzed using the free-involved listening technique and the note-taking technique. The findings of the data generated in this study as a whole amounted to 41 data on the form of directive speech acts and their functions. Data on the use of directive speech acts can be broken down as follows: (1) the form of command directive speech acts as much as 8 data; (2) form of request directive speech act as much as 15 data; (3) the form of directive solicitation speech acts as much as 5 data; 4) the form of directive advice speech acts as much as 5 data; 5) the form of critical directive speech acts as much as 3 data; and (6) form of prohibitive directive speech act as much as 5 data.